2022
DOI: 10.1590/0034-7167-2021-0001
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of healthcare students on organ and tissue donation for transplantation

Abstract: Objectives: to analyze the opinions of healthcare students on organ and tissue donation for transplantation. Methods: qualitative document analysis study, using the records of a database and analyzing data from two perspectives: 1) Lexical analysis, with the IRAMUTEQ software, and 2) Thematic content analysis. Results: from the analysis, 3 main categories were generated: 1) Organ and tissue donation as an act of love for others and an opportunity of a new beginning; 2) Clarification and awareness on organ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The importance of educating the public to increase organ donation is vital, as is the need to ensure that undergraduate students have an awareness and understanding of the issues regarding organ donation [ 1 ]. To support these efforts, it has been identified that educating students about organ donation at schools and colleges can have a positive effect on their views regarding organ donation [ 41 , 42 , 43 , 44 , 45 ]. Therefore, Timar et al suggest that education be provided by presenting information to student groups and classes through special programs that encourage students to discuss organ donation and the process [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of educating the public to increase organ donation is vital, as is the need to ensure that undergraduate students have an awareness and understanding of the issues regarding organ donation [ 1 ]. To support these efforts, it has been identified that educating students about organ donation at schools and colleges can have a positive effect on their views regarding organ donation [ 41 , 42 , 43 , 44 , 45 ]. Therefore, Timar et al suggest that education be provided by presenting information to student groups and classes through special programs that encourage students to discuss organ donation and the process [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Normally, families respect the wishes of the deceased when these have been expressed [ 9 ]. Therefore, it is very important for people who are in favour of donating their organs to communicate their wishes to family members, taking into account the presumed consent law established in Spain in which the family decision is taken into account [ 26 , 27 ]. When a family is faced with the donation of a family member’s organs, they find themselves at a time of mourning when making this decision is complicated [ 28 ].…”
Section: Discussionmentioning
confidence: 99%